Transforming Ethiopia’s Climate Information Services Ecosystem: From Fragmented Efforts to Integrated, Inclusive and Actionable Systems for Climate-Resilient Agriculture - Ahmed, Jemal Seid; Degefie, Degefie Tibebe; Teshome, Asaminew; Grossi, Amanda; Lemma, Esayas; Gebeyehu, Temesgen; Desta, Lulseged Tamene; Ghosh, Aniruddha (2025)
Climate information is increasingly recognized as a strategic public good essential for building climate-resilient agricultural systems. In Ethiopia, where livelihoods and national growth heavily depend on rain-fed smallholder farming, the effective generation, translation, and use of climate information have direct implications for food security, economic stability, and adaptation capacity. This policy working paper positions Climate Information Services (CIS) not just as a technical product but as a systemic enabler of risk-informed decision-making. It examines how fragmented institutions, weak coordination, and uneven access hinder the transformation of climate data into actionable, equitable, and scalable services. Anchored in the national policy framework—particularly the Climate Resilient Green Economy (CRGE) Strategy and the National Framework for Climate Services (NFCS)—the paper views CIS as an integrated ecosystem connecting scientific production with user demand through participatory and digital innovation pathways. Drawing on evidence and lessons from the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) program, it identifies the systemic conditions needed to make climate information operationally relevant, institutionally supported, and socially inclusive. Beyond identifying constraints, the paper promotes a policy vision for embedding CIS within Ethiopia’s broader agricultural transformation agenda. It emphasizes the need for long-term investment in data infrastructure, co-production platforms, and digitally enabled public-private partnerships that strengthen the national extension system and empower local communities. By framing CIS as adaptive infrastructure rather than ad-hoc projects, the study highlights its crucial role in achieving climate-resilient growth and sustainable rural livelihoods.